Certain aspects of the application of the subjective limitation period in proceedings brought by a competent public authority to hold controlling persons of the debtor subsidiarily liable outside bankruptcy proceedings - Leonid Eduardovich Vasilev (Юридические исследования, 2026)
This study examines the commencement of the three-year subjective (knowledge-based) limitation period for claims by the competent public authority to hold persons controlling the debtor subsidiarily liable outside bankruptcy proceedings after a bankruptcy petition is returned for lack of funds to finance the proceedings. It considers relevant legal relations, civil and bankruptcy law, case law, and scholarship on limitation of actions. Particular attention is paid to the actio nata rule and the distinction between accrual of the cause of action and the authority’s actual or constructive knowledge of the operative facts giving rise to the claim. It also addresses the authority’s ability to identify formally designated and concealed de facto controllers and evidence of when the authority learned of the tort’s constituent elements. The methodology combines doctrinal, systemic, and teleological methods with case-law analysis and synthesis to compare civil and bankruptcy legislation, scholarship, and judicial reasoning. The study’s original contribution lies in demonstrating the independent regulatory function of the three-year subjective limitation period. Current case law makes it difficult for controlling persons to raise the authority’s failure to sue in time as a limitations defense. The return of a bankruptcy petition for lack of funding makes the claim procedurally available but does not prove the authority’s knowledge of all operative facts establishing a specific controller’s liability. It proposes a differentiated approach to commencement based on the controller’s status, the nature of control, and information available to the Federal Tax Service of Russia. Actual or constructive knowledge must be established by evidence in each case, not solely by the date of the court order returning the petition. Finally, Article 204 of the Civil Code of the Russian Federation may be applied to account for time during which the bankruptcy petition was pending when calculating the subjective limitation period.